EDUKASI MANUAL MATERIAL HANDLING UNTUK PENCEGAHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA INDUSTRI KATERING DI DESA BANGUNTAPAN, BANTUL - Helfi Agustin; Machfudz Eko Arianto; Sayid Muhammad M.Idrus; Adella Fajrianty; Nurrohmah Nurrohmah; Meilana Nawang S; Ninda Yudhistira; Aqilla Padya P (Universitas Islam Indonesia, 2020)
One of Occupational safety and health (OSH) problem in catering is related to ergonomics. Lifting, lowering, pushing, pulling and carrying loads, done incorrectly or the use of tools that are not ergonomic, will pose a risk of injury to workers. The working process in catering starts from the preparation of ingredients; food is lifted from the market to temporary storage, then during the cooking process; lifting pots containing food from the stove, after the food is cooked; lifting food that to be distributed to customers affects musculoskeletal. Musculoskeletal risk factors in the catering business are long working hours, repetitive work with the same posture when preparing food, kitchen design, and unergonomic equipment, also limited workplace. Prevention efforts are important to prevent catering workers from Occupational Diseases, especially musculoskeletal disorder. Community service was provided to catering business owners and workers in the village of Banguntapan, Kab. Bantul. Based on community diagnosis, workers generally complain of illness. Aims to give awareness about risk and how to prevent musculoskeletal disorders by lifting weights properly. The method was counselling by poster media. Persuasive communication was carried out to convey the important contribution of all parties in enforcing OSH. Activities were going well, managers and workers understood and can practice how to lift weights properly. This community service is an effort to empower people to increase their knowledge and care in realizing an ergonomic work environment concept.